2011
DOI: 10.3126/jowe.v5i0.4595
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and diversity of zooplankton in relation to physico-chemical characteristics of water of Santragachi Jheel, West Bengal, India

Abstract: In the present study efforts have been made to ascertain the seasonal abundance and population dynamics of zooplankton community and its relationship with physico-chemical factors of the water bodies of Santragachi Jheel in the District Howrah, W.B., INDIA. The zooplankton abundance showed distinct seasonal or temporal variation in the Jheels. A total of 18 species belonging to 12 families and 15 genera were recorded. The population density of total zooplankton showed summer maxima in the Jheel. Maximum abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Flies species richness in investigated area is a key measure not only for biological status but also for ecosystem stability (Ciss et al, 2013). Patra et al (2011) showed that the species richness ranges between 1 and 5 shows moderate pollution, where larger index indicates more healthy water body but when it tends towards 1 means increase pollution and damage should be suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Flies species richness in investigated area is a key measure not only for biological status but also for ecosystem stability (Ciss et al, 2013). Patra et al (2011) showed that the species richness ranges between 1 and 5 shows moderate pollution, where larger index indicates more healthy water body but when it tends towards 1 means increase pollution and damage should be suspected.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on copepods that, according to Rajagopal et al (2011) and Ekpo (2013), play an integral role and serve as bioindicators of water pollution (Mukhopadhyay et al 2000). Indeed, species variation, distribution and abundance of zooplankton highly depend on the chemical and physical properties of water (Patra et al 2011). The species diversity index is a relevant tool for water quality assessment and a basis for biomonitoring by evaluating the structural complexity of zooplankton assemblages (Jafari et al 2011;Patra et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, species variation, distribution and abundance of zooplankton highly depend on the chemical and physical properties of water (Patra et al 2011). The species diversity index is a relevant tool for water quality assessment and a basis for biomonitoring by evaluating the structural complexity of zooplankton assemblages (Jafari et al 2011;Patra et al 2011). In the present study, the Shannon-Wiener index (H 0 ) for copepods was fairly low: H 0 was ,1.5 bits individual À1 for 55% of stations, including most northern stations (S1-10), except S3, S5 and S10, which had pioneer communities at the colonisation stage, and ranging between 1.5 and 2.5 bits individual À1 for the other stations, demonstrating a transition ecosystem at the diversification stage (Shannon and Weaver 1963).…”
Section: Discussionmentioning
confidence: 99%
“…These taxa include littoral, pelagic and benthic species, which perform key roles in the food web. The changes in population density, species richness and community structure of microcrustaceans (Cladocera and Copepoda) are mostly affected by physicochemical conditions and biological factors of the freshwater in which they live (Patra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%